A clinicopathological study of squamous cell carcinoma of oral cavity and oropharynx in non-smoker and non-drinker patients - Mehmi, Namrita; Bhagat, Sanjeev; Kaur, Navneet; Singh, Ravinder (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: To describe the clinicopathological variables of the Squamous cell carcinoma (SCC) of oral cavity and oropharynx in non-smoker and non-drinker patients (NSND). Methods: A retrospective review of thirty NSND patients with proven SCC of oral cavity and oropharynx in ENT department at Government Medical College Patiala. Data collected included demographics, aetiological factors, site, symptoms, nodal metastasis, histopathological grading and TNM staging at presentation. Results: In oral cavity cancers, patients presented commonly in 4th decade whereas in oropharynx, commonly in 6th decade. NSND patients were more likely to be female, male female ratio being 43:56. In NSND women, 82% had oral cavity SCC and 18% had oropharyngeal SCC. 13% of NSND patients reported sharp tooth, 10% reported regular environmental exposure, and 10% reported occupational exposure followed by lichen planus (6.67%). In oral cavity SCC, maximum incidence was that of oral tongue (59.1%) and in oropharyngeal SCC, base of tongue (62.5%) was most commonly involved. Overall, well differentiated SCC predominated in both oral cavity and oropharyngeal carcinoma in our study. In oral cavity SCC, maximum patients presented in early tumor staging i.e T1 and T2 (81.8%) and early overall staging (stage I and II).In oropharyngeal SCC, maximum patients presented in advanced tumor staging i.e T3 and T4 (62.5%) and advanced overall staging (stage III, IV). Conclusions: In NSND patients, potential factors like sharp tooth, environmental smoke, occupational exposure and lichen planus may contribute to SCC in oral cavity and oropharynx.